Pilot study of online ante-mortem inspection for emergency slaughtered cattle in Denmark - Maybritt Kiel Poulsen; Lis Alban; Lis Alban; Annette Dresling (Frontiers in Veterinary Science)
According to the EU legislation, bovines subjected to emergency slaughter must undergo a physical ante-mortem inspection (AMI) on the farm before slaughter if the meat is to be placed on the market for human consumption. This pilot study examined the performance of online AMI using a software system that enabled a video consultation between the veterinarian and the farmer. During 2022–2023, 38 bovines, possibly eligible for emergency slaughter, were included in the study. A comparison between online and physical AMI was carried out. Furthermore, a comparison was made between two different veterinarians (vet.1 and vet.2) about the performance of AMI for each bovine. The results showed that vet.1 considered the online judgement as adequate for 95% of the cases in the study, whereas vet.2 considered 90% adequate. Moreover, the agreement between the two veterinarians was high (accuracy = 90%), both regarding the adequacy of the system and the eligibility of the bovine for slaughter. Prerequisites for using online AMI are suitable video equipment, a reliable internet connection and sufficient light. Furthermore, the use of a checklist will help to assure standardized online AMI. Saving the recorded videos will reduce the risk of fraud and enable training and calibration of veterinarians. In conclusion, online AMI of bovines destined for emergency slaughter will, in most cases, be comparable to physical AMI on-farm. However, the use of online AMI presupposes a change of the EU legislation.